Sox11 regulates mammary tumour-initiating and metastatic capacity in Brca1-deficient mouse mammary tumour cells - Siu Man Tsang; Hyojin Kim; Erik Oliemuller; Richard Newman; Naa-Anyima Boateng; Naomi Guppy; Beatrice A. Howard (Disease Models & Mechanisms, 2021)
Little is known about the role of Sox11 in the regulation of mammary progenitor cells. Sox11 is expressed by mammary bud epithelial cells during embryonic mammary gland development and is not detected in mammary epithelial cells after birth. As Sox11 is an oncofetal gene, we investigated the effects of reducing Sox11 levels in embryonic mammary progenitor cells and found that Sox11 regulates proliferative state, stem cell activity and lineage marker expression. We also investigated the effect of reducing Sox11 levels in two transplantable Brca1-deficient oestrogen receptor-negative mouse mammary tumour cell lines, to assess whether Sox11 regulates similar functions in tumour progenitor cells. When Sox11 levels were reduced in one Brca1-deficient mammary tumour cell line that expressed both epithelial and mesenchymal markers, similar effects on proliferation, stem cell activity and expression of lineage markers to those seen in the embryonic mammary progenitor cells were observed. Orthotopic grafting of mammary tumour cells with reduced Sox11 levels led to alterations in tumour-initiating capacity, latency, expression of lineage markers and metastatic burden. Our results support a model in which tumours expressing higher levels of Sox11 have more stem and tumour-initiating cells, and are less proliferative, whereas tumours expressing lower levels of Sox11 become more proliferative and capable of morphogenetic/metastatic growth, similar to what occurs during embryonic mammary developmental progression.